The shaping of socio-economic systems : the application of the theory of actor-system dynamics to conflict, social power, and institutional innovation in economic life /: the application of the theory of actor-system dynamics to conflict, social power, and institutional innovation in economic life. (2014) - Baumgartner, Thomas (Thomas Martin); Burns, Tom R; DeVille, Philippe
No abstract available